Implementasi Electronic Customer Relationship Management menggunakan Metode Framework of Dynamic berbasis Web - Wicaksono, Erwin; Fauziah, Fauziah; Hidayatullah, Deny (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2021)
The purpose of this study is to build soft devices for electronic customer relationship management (e-CRM) with the Framework of Dynamic method which will facilitate customer relationship management that can help relationships between stores and customers so that customers can enjoy and feel comfortable with the store services that can eventually be formed. In implementing this software, the author uses the system development lifecycle (SDLC) method then produces a web-based e-CRM prototype with PHP programming languages and MySQL DBMS. This e-CRM prototype has been tested in terms of verification, validation, and prototype testing. To design this system Use Cases, ERD, LRS, Class Diagrams, and Sequence Diagrams are used. From the test results, it can be seen that the e-CRM prototype has been successful and is in accordance with the planning objectives. The result of this Marketplace Design is as a forum to make it easier for shop owners in the field of Building Materials and the like to market the products they have here.Keywords:e-CRM, Framework of Dynamic CRM, Customer, System Development Life Cycle.